2012
DOI: 10.3109/00016357.2012.680907
|View full text |Cite
|
Sign up to set email alerts
|

Changes in adolescents' oral health status following oral health promotion activities in Tanzania

Abstract: The intervention activities did not show any effect with respect to dental caries, calculus and plaque status among the students investigated. Compared with the control group, more favorable changes in the intervention group occurred with respect to bleeding on probing, suggesting a weak but positive effect on students' oral hygiene status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 148 publications
(204 reference statements)
4
23
0
Order By: Relevance
“…34 Furthermore, improvements in the gingival status were observed among schoolchildren from health-promoting schools in Tanzania but not among those from the control schools. 33 Our findings corroborate the potential benefits of health-promoting schools on adolescent's oral health.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…34 Furthermore, improvements in the gingival status were observed among schoolchildren from health-promoting schools in Tanzania but not among those from the control schools. 33 Our findings corroborate the potential benefits of health-promoting schools on adolescent's oral health.…”
Section: Resultssupporting
confidence: 80%
“…Children from health-promoting schools had significantly better OHRQoL and less oral impacts on cleaning teeth compared to children from control schools. 32,33 Health-promoting schools have been related to the improvement of children's oral health. The prevalence of decayed teeth and dental trauma was lower in health-promoting schools in Brazil compared with those without health promotion programmes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed in studies of D'Cruz et al, Pakpour et al, Angelopoulou et al, Pakpour et al, Yekaninejad et al and Mbawalla et al that oral health‐educating intervention can be effective in improving the gingival health and reducing plaque levels. D'Cruz et al reported that the mean of plaque index and the gingival index scores was improved after 9 months of intervention in the intervention group compared to the control group.…”
Section: Resultsmentioning
confidence: 68%
“…Post hoc Tukey's test showed that this increase was statistically significant ( P < .001). Mbawalla et al observed that bleeding and plaque decreased after intervention adolescent more than the control group, and these changes were statistically significant (0.5 vs 0.3, P < .05). Yekaninejad et al reported that gingival health in children in comprehensive intervention group increased significantly (OR = 0.60, 95% CI: 0.53‐0.67; P = .025) comparing to the control group.…”
Section: Resultsmentioning
confidence: 92%